Scientific and Technical Issues in the Management of Spent Fuel of Decommissioned Nuclear Submarines - Sarkisov, Ashot; Tournyol du Clos, Alain (NATO Science Series II: Mathematics, Physics and Chemistry, Mathematics, Physics and Chemistry, 2006)
Similar to the three previous publications, which collected the materials of the NATO-Russia ARWs held in Moscow in 1995, 1997 and 2002, this fourth book addresses a very important challenge of the present - complex decommissioning of the nuclear-powered vessels taken out of service and environmental rehabilitation of the centers of basing and everyday running of different-type nuclear vessels. The fourth book specifically focuses on the scientific and technical problems of management of naval spent nuclear fuel and radioactive waste. Some papers address the first results of the "Strategic Master-plan ("Master-plan") for complex decommissioning of Russian nuclear-powered vessels" developed in Russia with active participation and large financial support of the international community. This fourth book, taken together with the papers of the three previous NATO ARWs published earlier, represents the most complete collection of materials on complex decommissioning of nuclear-powered vessels including the spent nuclear fuel management-related challenge.